Crosstalk between hypertension and diabetes: focusing on pregnancy and offspring. A systematic review - Alejandra, Medina-Hernández; Ricardo, Espinosa-Tanguma; Guadalupe, Donjuán-Loredo (Frontiers in Physiology, 2025)
IntroductionThe coexistence of diabetes mellitus (DM) and hypertension (HT) is very common; both pathologies seem to share different mechanisms such as insulin resistance (IR), endothelial dysfunction, increase in reactive oxygen species (ROS), among others. Furthermore, exposure to hyperglycemia during gestational development has been defined as a risk factor for cardiovascular disease (CVD) in adulthood. However, the mechanisms involved in this “prenatal programming” are still unclear. This review aims to identify the mechanisms involved in the relationship between DM and HT, both in their coexistence and in the development of HT in offspring derived from gestational diabetes (GD). There are no reviews that comprehensively cover both the link between HT and DM as well as the risk factors in mothers with GD and the cardiovascular effects in their offspring.MethodsA search of published studies reporting HT in offspring of diabetic pregnancies, either in animals or humans, prevalence and pathophysiological mechanisms of binomial hypertension-diabetes (HT/DM), mechanisms, metabolic alterations, DM and HT in pregnancy was done. Inclusion criteria were studies investigating the cardiovascular effects of GD on offspring, studies in animal models or humans, reviews and meta-analyses.Results87 studies were included. IR is the main common factor between the presence of DM and the development of HT, in addition to inflammatory processes. Maternal pathology before pregnancy favors the development of diabetes and HT during pregnancy. Animal studies have shown that 100% of the offspring of mothers with GD have HT, mostly after 12 weeks of age. In human studies, there is a significant difference in the blood pressure (BP) levels of the offspring of mothers with gestational hyperglycemia compared with control mothers from the age of 2 years. Several mechanisms such as structural changes in the arterial wall, endoplasmic reticulum (RE) stress, increase in ROS and decrease in nitric oxide (NO) synthesis are proposed as some of the possible culprits.ConclusionCurrent evidence shows that the interaction between DM and HT occurs through mechanisms that they share in their pathogenesis, that is, the presence of one lead to the other and the hyperglycemia to which infants are exposed in utero makes them more susceptible to CVD.